Inflammatory-induced spinal dorsal horn neurons hyperexcitability is mediated by P2X4 receptors. (May 2018) - Aby, Franck; Whitestone, Sara; Landry, Marc; Ulmann, Lauriane; Fossat, Pascal
Abstract: Introduction: Purinergic ionotropic P2X receptors (P2RX) are involved in normal and pathological pain transmission. Among them, P2X4 are expressed in dorsal root ganglion and in the spinal cord. Their activation during nerve injury or chronic peripheral inflammation modifies pain sensitivity that leads to the phenomenon of allodynia and hyperalgesia. Objectives: We study here, in vivo, the role of P2X4 on the excitability of dorsal horn neurons (DHNs) in naive or pathological context. Methods: We recorded DHNs in vivo in anesthetized wild-type or P2RX4 −/− mice. We measured nociceptive integration and short-term sensitization by DHNs both in naive and inflamed mice. Results: Our results indicate that P2X4 alter neuronal excitability only in the pathological context of peripheral inflammation. Consequently, excitability of DHNs from inflamed P2RX4 −/− mice remains similar to naive animals. Conclusion: These results confirm the prominent role of P2X4 in inflammatory pain context and demonstrate that P2X4 are also involved in the hyperexcitability of DHNs.